Implementation of Social Sciences Education in Improving Students' Critical Thinking Abilities - Yuniarto, Bambang; Ramadhan, Ilyasa; Monika, Dea; Lutfiah, Syifa; Nurfau Darajatin, Rifa (International Journal Labs, 2024)
Critical thinking skills are essential in educational institutions, especially social studies education. Social studies education mainly focuses on developing students' critical thinking skills. This research explores the methods used in social studies learning to support students' critical thinking abilities. The method used in this research is to use a qualitative description approach, using primary and secondary data collection techniques. The primary data collection technique involves interviewing education experts. In contrast, secondary data is obtained by exploring information through scientific works such as articles, books, and educational documents. The results of this research are that in improving students' critical thinking skills, social studies learning can combine learning methods such as discussion-based learning methods, case studies, social research projects, assessment of critical thinking skills, and the use of technology in social studies learning. The implications of this research suggest that educational institutions should prioritize the integration of these diverse learning methods to foster critical thinking skills in students, thereby enhancing their overall academic performance and preparing them for complex problem-solving in real-world scenarios